Life Cycle Risk Assessment of Urban Rail Equipment Based on Reliability Analysis - WANG Junzhe; ZHU Lin; LIU Zhigang; TAO Yijun; HUANG Yuanchun (Chengshi guidao jiaotong yanjiu)
［Objective］ The high reliability of urban rail transit system equipment is the cornerstone and guarantee for maintaining the safe and stable operation. Due to the rapid increase in operating mileage and the continuous expansion of network line capacity in recent years, the operational risks of urban rail transit are increasing every day, and the impact of reliability on safety risks is receiving increasing attention from the industry. ［Method］ Based on the impact of lifecycle events on reliability, urban rail transit equipment is divided into lifecycle stages (operation and maintenance phase). According to historical failure data, a data statistical model assisted by a mechanism model is established, and relevant reliability indicators are characterized through Minitab software. Based on the risk matrix method, the mapping relationship between reliability and lifecycle stages is characterized, and an equipment risk assessment model considering lifecycle stages is established. ［Result & Conclusion］ Taking the vehicle bogie wheelset axle box assembly as a case study, according to the vehicle specialized maintenance content and cycle requirements, the daily operation stages are categorized into four periods: stable operation, early failure, late failure, and replacement; the failure interval time is tested for fitting, and the three-parameter Weibull distribution is selected to represent its reliability characteristic function; each phase is mapped and assigned values through the reliability characteristic function. Based on the risk matrix method, the risk assessment levels of the vehicle bogie wheelset axle box assembly at each stage are obtained, and then the risk assessment results for each stage are output respectively. Risk levels for each stage are marked as R5, R3, R1, and R1.